DAHANCA 28: A phase I/II feasibility study of hyperfractionated, accelerated radiotherapy with concomitant cisplatin and nimorazole (HART-CN) for patients with locally advanced, HPV/p16-negative squamous cell carcinoma of the oropharynx, hypopharynx, larynx and oral cavity. (July 2020) - Saksø, Mette; Jensen, Kenneth; Andersen, Maria; Hansen, Christian Rønn; Eriksen, Jesper Grau; Overgaard, Jens
Highlights: Intensification of RT is needed to improve tumor control in high-risk HNSCC. Dose escalation is possible using hyperfractionation. Combining hyperfractionation, acceleration, cisplatin and nimorazole was feasible. Toxicity was slightly enhanced compared to standard chemo-radiotherapy, but manageable. The combination schedule yielded favorable tumor control. Abstract: Background: A phase I–II study to evaluate the feasibility and efficacy of intensified, primary radiotherapy (RT) for Locally Advanced Head and Neck Squamous Cell Carcinoma (LAHNSCC) employing dose escalation by hyperfractionation, acceleration of treatment time, concomitant chemotherapy and hypoxic modification. Methods: Patients with HPV/p16- LAHNSCC receiving primary hyperfractionated, accelerated RT, 76 Gy/56 fx, 10 fx/week for 5½ weeks, concomitant weekly cisplatin (40 mg/m 2 ) and nimorazole (HART-CN) were included. Primary endpoint was locoregional failure (LRF). Secondary endpoints were overall survival (OS) and toxicity. Results: 50 patients received HART-CN from 2013 to 2017. Median age was 60 years. Most patients had stage IV hypo- or oropharynx cancer with a heavy smoking history. All oropharyngeal cancers were HPV/p16-negative. Ninety-eight percent of patients completed RT, but compliance to cisplatin and nimorazole was lower. Median observation time was 44 months. LRF was diagnosed in 10 patients. All LRFs were in the high-dose CTV. The 3-year actuarial LRF was 21%, and OS was 74%. The peak incidence of acute toxicity showed that 67% of patients experienced severe dysphagia, 61% severe mucositis, and 78% were equipped with feeding tubes. Late severe morbidity was seen in 7 of 29 recurrence-free patients with at least 3 years of followup, who presented with either severe dysphagia ( n = 2), severe xerostomia ( n = 1), severe fibrosis of the neck ( n = 3) or osteoradionecrosis ( n = 1). Three were still tube dependent. Conclusion: HART-CN is feasible in patients with HPV/p16- LAHNSCC in good health. Although acute toxicity was pronounced, the proportion of patients with late toxicity was acceptable and outcome at 3 years encouraging.